The Role of MARPOL Annex V Implementation in Reducing Marine Litter in Indonesia: Challenges and Opportunities - Wanadi , M Adil; Schouten, Femmy Sofie; Handoko , Wisnu; Seno , William; Rizal, Yus; Indra, Guntur Tri (Meteor STIP Marunda, 2025)
The implementation of MARPOL Annex V, which governs ship-generated waste to prevent marine pollution, remains inconsistent in Indonesia despite its ratification into national law. This study investigates compliance gaps, operational challenges, and systemic barriers that hinder effective enforcement aboard Indonesian-flagged vessels. The research identifies three primary issues: low crew awareness due to inadequate training, limited port waste reception facilities, and weak supervision and law enforcement by maritime authorities. Findings reveal a disconnect between policy and practice, with only 30% of surveyed vessels meeting waste segregation and disposal requirements. To address these shortcomings, this study proposes a multi-stakeholder strategy combining stricter law enforcement, standardized crew certification programs, and investments in port waste infrastructure. These recommendations aim to enhance Indonesia’s alignment with global marine protection standards under MARPOL Annex V, while offering insights for other developing maritime nations.